FAKTOR PENARIK DAN PENDORONG TRANSFORMASI TENAGA KERJA DI KAMPUNG AIMASI - Rissa Latul Alifah; Djuliati Dampa; Deasi Mayawati (Department of Social Economic Agriculture, Faculty of Agriculture, University of Papua, Manokwari, West Papua, Indonesia, 2021)
The existence of push and pull factors for the transformation of the agricultural workforce is a reflection of the condition of the non-agricultural sector which is considered to be more profitable and / or the condition of the agricultural sector which is no longer profitable. The research aims to examine the pull and push factors of labor transformation in Aimim Village and identify the types of non-agricultural sector jobs carried out by transformed workers. The respondent was determined using the snowball technique (snowball). The method of data analysis obtained in this study is processed using tabulation analysis which is the driving factor for wages, farm income, land area, risk. Attractor factors for non-agricultural income, working conditions, education level